2017
DOI: 10.4088/jcp.17m11777
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Valbenazine in Participants with Tardive Dyskinesia

Abstract: Background: Valbenazine, a highly selective vesicular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 9 publications
7
47
0
1
Order By: Relevance
“…Valbenazine has shown to improve TD in the KINECT 3 trial [46]. In this study parkinsonism was an exclusion criteria, and results disclosed no differences between treatment groups both after 6 weeks and after a 1-year period in parkinsonism as assessed by the Simpson-Angus-Scale [47]. With a similar mechanism of action, deutetrabenazine has showed in 2 studies, one in a population with chorea associated with Huntington's Disease and other in patients suffering TD similar DIP rates in both treatment and placebo arms.…”
Section: Pathophysiology and Causal Agentsmentioning
confidence: 61%
See 1 more Smart Citation
“…Valbenazine has shown to improve TD in the KINECT 3 trial [46]. In this study parkinsonism was an exclusion criteria, and results disclosed no differences between treatment groups both after 6 weeks and after a 1-year period in parkinsonism as assessed by the Simpson-Angus-Scale [47]. With a similar mechanism of action, deutetrabenazine has showed in 2 studies, one in a population with chorea associated with Huntington's Disease and other in patients suffering TD similar DIP rates in both treatment and placebo arms.…”
Section: Pathophysiology and Causal Agentsmentioning
confidence: 61%
“…Following this results FDA-approval took place during the same year [128]. The 1-year follow-up study showed no risk of suicidal ideation worsening akathisia or parkinsonism [47].…”
Section: Prevention and Treatment (Figure 2)mentioning
confidence: 89%
“…A long-term study (KINECT 3 Extension) reinforced these outstanding results about efficacy, safety and tolerability [16]. The most common adverse events were headache, urinary tract infection, diarrhea, dizziness, suicidal ideation and depression [16]. Moreover, a further analysis of these studies confirmed the statistically significant improvements in TD severity both overall and in separate body regions [17].…”
Section: Valbenazinementioning
confidence: 83%
“…In addition to efficacy, VBZ showed a favorable side effect profile and it was well tolerated by patients. A long-term study (KINECT 3 Extension) reinforced these outstanding results about efficacy, safety and tolerability [16]. The most common adverse events were headache, urinary tract infection, diarrhea, dizziness, suicidal ideation and depression [16].…”
Section: Valbenazinementioning
confidence: 93%
“…Die Verwendung des GABA-A-Agonisten Clonazepam in der Therapie der TD wurde in den 1970er-und 1980er-Jahren untersucht, was schließlich in der Publikation einer sehr kleinen RCT im Jahr 1990 resultierte. [53,56,57,58]. Für Deutetrabenazin existieren zwei hochwertige RCT über 12 Wochen, die deutliche Effekte gemessen am AIMS zeigen konnten.…”
Section: Risikofaktoren Und Präventionunclassified